Intervention through an intelligent technological platform for socio-emotional development and health promotion in adolescents with Type 1 Diabetes Mellitus (emoTICare): A study protocol for randomized controlled trial - Javier Martín-Ávila; Esther Rodríguez-Jiménez; Selene Valero-Moreno; José-Antonio Gil-Gómez; Inmaculada Montoya-Castilla; Marián Pérez-Marín (PLoS ONE, 2025)
Background During adolescence, individuals face various challenges that require adequate psychosocial and emotional adjustment. Additionally, the presence of a chronic illness during this stage, such as Type 1 Diabetes Mellitus (T1DM), introduces additional medical and psychological needs, which can increase vulnerability. In this context, serious games emerge as a promising tool to address educational and psychoemotional aspects while maintaining the motivation and playability typical of a video game. Currently, no technological tool simultaneously addresses both the educational and psycho-emotional needs of adolescents with T1DM. Aim This study aims to design and validate a psychological intervention program using a technological platform that incorporates artificial intelligence. Through the serious game emoTICare, the goal is to promote physical and emotional health in adolescents with T1DM by enhancing the development of socio-emotional skills. Method Test this tool, adolescents with T1DM will be recruited through diabetes associations across Spain. The participants, 372 adolescents aged between 12 and 16, will be randomly assigned to either a control or an experimental group. The experimental group will complete the emoTICare program. Over six weeks, participants will engage in psychoeducational activities using the tools provided by the serious game. Data Will be collected at three points: baseline (T1) and after six weeks (T2) (for the control group, T2 will be at the same time as the experimental group’s post-intervention), and aT3 (after six months of T2). The program’s effectiveness will be analyzed using various statistical packages. Results and conclusions The study hypothesizes that adolescents will maintain or improve their physical and emotional health indicators following the emoTICare program. Specifically, statistically significant improvements (p ≤ .05) are expected in the following variables: health-related quality of life, social skills and communication, emotional awareness, resilience, self-esteem, and coping and problem-solving abilities. Additionally, a statistically significant reduction (p ≤ .05) is anticipated in variables related to the perceived threat of the disease, as well as emotional and behavioral problems. The experimental group is expected to present improvements in all these areas when comparing pre- and posttreatment evaluations, and also in comparison to the control group on the waiting list.